Properties of composites based on chemically treated hemp woody core and epoxyurethane containing epoxidized soybean oil - T. F. Samoilenko; L. M. Yashchenko; N. V. Yarova; O. O. Brovko (Хімія, фізика та технологія поверхні, 2024)
In last two decades the intensive growth in the number of publications devoted to plant fibers as reinforcements for polymer matrices is observed. Considering ecological issues natural fibers are recognized as an appealing alternative to synthetic ones. Unlike hemp fiber, which is frequently used for given needs, its by-product named hemp woody core (HWC) has not yet gained much scientific attention in this sphere. Nevertheless, owing to the set of its unique properties HWC is also may be a promising filler. Application of HWC in composites would additionally contribute to its proper utilization. However, among the distinctions of lignocellulosic reinforcements is their hydrophilicity that requires to be reduced to ensure strong interface interaction with the matrix and good durability of the resulting composites. Herein, mercerization (alkali treatment) and/or subsequent modification of HWC with epoxidized soybean oil (ESO) or 3-aminopropyltriethoxysilane (APS) was used for this purpose. Si-containing epoxyurethane polymer matrix was synthesized from sodium silicate, polyisocyanate and ESO as epoxy component. Four series of molded samples with high plant filler content (60 wt. %) were elaborated. The results of contact angle and water uptake measurements showed that all applied types of treatment led to hydrophobization of the surface. Thus, the values of contact angles of composites with modified HWC exceeded 90 °, and their surface energy was lower than the one of neat samples. Regardless of quite high polarity of composites containing silanized HWC due the presence of amino and silanol groups, the formation of covalent bonds between filler and APS coupling agent turned out to be crucial for such characteristics as water resistance and mechanical performance. Particularly, equlibrium moisture content decreased by 31 % compared to that of the samples with pristine HWC, whereas tensile and flexural strength improved by 19 and 65 %, respectively. The highest microbial stability of the specimens with silane treated filler estimated within soil burial test is another evidence of enhanced interfacial adhesion in this case.